Gamma Knife Radiosurgery Long-Term Efficacy and Safety for Glomus Jagulare Tumors: A Single Institution Experience and Review of the Literature (British Journal of Multidisciplinary and Advanced Studies, 2024)
Glomus jugulare tumors (GJTs) are benign, slowly growing tumors, highly vascular, with the potential to infiltrate neurovascular structures. Surgical treatment is usually associated with high morbidity and even death. Gamma Knife radiosurgery (GKRS) has been established as an effective treatment option. This retrospective study aims to report and confirm GKRS.'s long-term effectiveness and safety for GJT patients. A total of 65 patients with GJTs were treated with GKRS, at the authors' center from 2005 to 2020, with a mean follow-up period of 87.7 months. The mean treated GJT volume was 5.4cc with a median prescription dose of 15Gy and a median maximum dose of 42.9Gy. Most patients were females (77%), and the median age at presentation was 48 years. The overall tumor growth control was 93.8% (61 patients) 39% of them achieved tumor size reduction. The overall clinical control was 90.8% (59 patients), and 40.7% achieved clinical improvement. The Actuarial tumor rate free of progression was 100% at 3 years, 91.5% at 5 years, and 86% at 10 years of follow-up. GKRS for GJTs typically results in high long-term tumor control and lower neurological morbidity than those associated with microsurgical resection, therefore should be consider as a dependable effective treatment option.